Torix Rickettsia are widespread in arthropods and reflect a neglected symbiosis. Issue 3 (25th March 2021) - Pilgrim, Jack; Thongprem, Panupong; Davison, Helen R; Siozios, Stefanos; Baylis, Matthew; Zakharov, Evgeny V; Ratnasingham, Sujeevan; deWaard, Jeremy R; Macadam, Craig R; Smith, M Alex; Hurst, Gregory D D
Abstract: Background: Rickettsia are intracellular bacteria best known as the causative agents of human and animal diseases. Although these medically important Rickettsia are often transmitted via haematophagous arthropods, other Rickettsia, such as those in the Torix group, appear to reside exclusively in invertebrates and protists with no secondary vertebrate host. Importantly, little is known about the diversity or host range of Torix group Rickettsia . Results: This study describes the serendipitous discovery of Rickettsia amplicons in the Barcode of Life Data System (BOLD), a sequence database specifically designed for the curation of mitochondrial DNA barcodes. Of 184, 585 barcode sequences analysed, Rickettsia is observed in ∼0.41% of barcode submissions and is more likely to be found than Wolbachia (0.17%). The Torix group of Rickettsia are shown to account for 95% of all unintended amplifications from the genus. A further targeted PCR screen of 1, 612 individuals from 169 terrestrial and aquatic invertebrate species identified mostly Torix strains and supports the "aquatic hot spot" hypothesis for Torix infection. Furthermore, the analysis of 1, 341 SRA deposits indicates that Torix infections represent a significant proportion of all Rickettsia symbioses found in arthropod genome projects. Conclusions: This study supports a previous hypothesis that suggests that Torix Rickettsia are overrepresented in aquatic insects. In addition, multiple methods reveal further putative hot spots of Torix Rickettsia infection, including in phloem-feeding bugs, parasitoid wasps, spiders, and vectors of disease. The unknown host effects and transmission strategies of these endosymbionts make these newly discovered associations important to inform future directions of investigation involving the understudied Torix Rickettsia .